Chironomus polonicus sp. n. (Diptera: Chironomidae) from southern Poland - Michailova, Paraskeva; Kownacki, Andrzej; Langton, Peter H. (Zootaxa, 2013)
The paper describes larval, pupal and adult morphology as well as the karyotype of Chironomus polonicus sp. n. from southern Poland. The material has been obtained from reared egg masses collected in Bolesław pool, near Kraków. The species belongs to the pseudothummi cytocomplex with 2n = 8 and chromosome arm combinations AE, BF, CD, G. Several homozygous inversions distinguish arm A of the new species from that of C. pseudothummi Strenzke. Arm F is similar to that of C. aprilinus Meigen and differs from it by few steps of homozygous inversions. Few morphological differences in the pupa and adult are also presented.